2008
DOI: 10.2975/31.4.2008.306.312
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Treatment Study.

Abstract: Security Disability Insurance (SSDI) beneficiaries with primary psychiatric impairments comprise the largest, fastest growing, and most costly population in the SSDI program. The Mental Health Treatment Study provides a comprehensive test of the hypothesis that access to evidence-based employment services and behavioral health treatments, along with insurance coverage, can enable SSDI beneficiaries with psychiatric impairments to return to competitive employment. It will also examine which beneficiaries choose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…The MMS intervention was composed of two parts: a systemic review of symptoms and functioning by an experienced nurse prior to each prescriber visit and an "algorithmic approach" to MMS that employed diagnosis specific decision trees. Frey et al (2011) found that the MHTS improved several employment, earnings, and health outcomes for treatment group members and that participation rates were generally strong among those offered services. Frey et al noted that the strong participation rates (14 percent of those solicited participated) potentially reflect high unmet demand for these types of services.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MMS intervention was composed of two parts: a systemic review of symptoms and functioning by an experienced nurse prior to each prescriber visit and an "algorithmic approach" to MMS that employed diagnosis specific decision trees. Frey et al (2011) found that the MHTS improved several employment, earnings, and health outcomes for treatment group members and that participation rates were generally strong among those offered services. Frey et al noted that the strong participation rates (14 percent of those solicited participated) potentially reflect high unmet demand for these types of services.…”
mentioning
confidence: 99%
“…However, these benefits came at significant intervention cost, as each treatment group member received $6,986 worth of services each year. Although the demonstration did not conduct a formal benefit-cost analysis, Frey et al (2011) noted that MHTS had impacts in other areas that would be important in assessing the net benefits of the demonstration. For example, MHTS created important service linkages to ensure that beneficiaries received and adhered to their prescription drug medication, as well as provided other mental health supports that had impacts elsewhere, including reduced hospitalizations.…”
mentioning
confidence: 99%
“…94 Recent data reveal that the proportion of SSDI awards for psychiatric disorders has increased from 11% in 1981 to 41% in 2006. 93 These startling figures suggest that while third parties often seek to raise the bar that defines the threshold for SMI, powerful financial incentives can drive both clinicians and patients to jump higher by overrating the severity and chronicity of functional impairments associated with mental illness. Unfortunately, this practice may disincentivize recovery, and could, ironically, result in denial of future health care coverage based on preexisting conditions.…”
Section: P XXIImentioning
confidence: 99%
“…92, p 253 of psychiatric symptoms, and psychotic symptoms in particular, 92 such that mental disorders have become the single largest source of disability, 93 with about one-third of mental health beneficiaries carrying a diagnosis of schizophrenia. 94 Recent data reveal that the proportion of SSDI awards for psychiatric disorders has increased from 11% in 1981 to 41% in 2006.…”
Section: P XXIImentioning
confidence: 99%
“…There have been numerous efforts to engage in QI focused on supported employment. Some have been highly effective, while others have been frustrated, mostly by organizational or fi nancial constraints (Drake et al, 2013;Frey et al, 2008Frey et al, , 2011Hamilton et al, 2013 ;McHugo et al, 2007 ).…”
Section: Quality Improvement For Evidence-based Practicesmentioning
confidence: 99%